2005
DOI: 10.1103/physrevb.72.214416
|View full text |Cite
|
Sign up to set email alerts
|

Surface criticality in random field magnets

Abstract: The boundary-induced scaling of three-dimensional random field Ising magnets is investigated close to the bulk critical point by exact combinatorial optimization methods. We measure several exponents describing surface criticality: ␤ 1 for the surface layer magnetization and the surface excess exponents for the magnetization and the specific heat, ␤ s and ␣ s . The latter are related to the bulk phase transition by the same scaling laws as in pure systems, but only with the same violation of the hyperscaling e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…To one-loop order they obey relation β 1 = 2β. Up to now the both magnetization exponents have been studied only for the 3D RFIM where numerical simulations give β = 0.0017 ± 0.005 [51] and β 1 = 0.23 ± 0.03 [42]. Thus, the ratio β 1 /β for the RF O(N ) systems in d > 4 is much smaller than for the 3D RFIM.…”
Section: The Surface Exponents To One-loop Ordermentioning
confidence: 99%
See 1 more Smart Citation
“…To one-loop order they obey relation β 1 = 2β. Up to now the both magnetization exponents have been studied only for the 3D RFIM where numerical simulations give β = 0.0017 ± 0.005 [51] and β 1 = 0.23 ± 0.03 [42]. Thus, the ratio β 1 /β for the RF O(N ) systems in d > 4 is much smaller than for the 3D RFIM.…”
Section: The Surface Exponents To One-loop Ordermentioning
confidence: 99%
“…The surface criticality of the RFIM has been studied numerically in Ref. [42]. It was also shown that the RF disorder on the surface of a 3D spin system with continuous symmetry destroys the long-range order in the bulk, and, instead, a QLRO emerges [43].…”
Section: Introductionmentioning
confidence: 99%